Analisis People, Process, Physical Evidence Terhadap Keputusan Konsumen Menggunakan Ekspedisi Lion Parcel - Retno Ayu Siska Wardani; Tarsisius Kana; Irfan Wildzan Muafa (Musamus Journal of Business & Management, 2021)
RETNO AYU SISKA WARDANI (2020). The Influence of People, Process and Physical Evidence on Consumer Decisions to Use Lion Parcel Merauke Expeditionary Services. Supervised by Tarsisius Kana SE., M.Si. This study aims to determine whether people influence consumer decisions to use the Merauke lion parcel shipping service. To find out which process affects consumer decisions to use the Merauke lion parcel shipping service. To find out Physical Evidence affects consumer decisions to use the Merauke Lion Parcel Expedition Service. To find out the effect of people, process and physical evidence have an effect on consumer decisions to use the Merauke Lion Parcel Expedition Service. The population in this study were consumers of the Merauke lion parcel expedition service with a population of 6,940 people and a sample of 99 people. The calculation of the Slovin 10% formula and uses the incidental (coincidence) sampling technique. This study uses a quantitative approach and multiple linear regression analysis with the SPSS version 23 application. From the results of multiple linear regression analysis, the equation Y=8.313+0.708(X1)+0.797(X2) 0.725(X3) is obtained. The results of hypothesis testing, namely the t test and the F test, show that the people, process and physical evidence variables have a positive and significant effect partially and simultaneously on purchasing decisions on the Merauke lion parcel expedition service. Evidenced by the value of thitung people(X1) 2.995> ttable 1.290 with a significant level of 0.003<0.10 so that Ho is rejected and Ha is accepted. The value of process tcount (X2) 4.085> ttable 1.290 with a significant level of 0.000<0.10 so that Ho is rejected and Ha is accepted. The value of tcount physical evidence (X3) 3,216>ttable 1.290 with a significant level of 0.002 <0.10 so that Ho is rejected and Ha is accepted. The value of Fcount 38.643> Ftable of 3.94 with a significant level of 0.000 <0.10 so that Ho is rejected and Ha is accepted. The value of Adjusted R Square is 0.535, which means that all independent variables together have an effect on purchasing decisions on Lion Parcel Merauke's shipping services. amounted to 53.5% while the remaining 46.5% was influenced by other variables not examined in this study.